Percolation transitions in d-wave superconductor–half-metallic ferromagnet nanocomposites - Krivoruchko, V.N.; Tarenkov, V.Y. (Физика низких температур, 2019)
Electrical transport properties of random binary networks composed of high-Tc superconductor Bi₂Sr₂Ca₂Cu₃O₆+x microparticles and half-metallic ferromagnet La₀.₆₇Sr0.₃₃MnO₃ (LSMO) nanoparticles have been investigated. Two resistive percolation transitions (superconductor–metal–semiconductor) have been observed for the nanocomposites with a volume fraction of the LSMO no more than 30%. The nanocomposites basic attributes (transition critical temperatures, current–voltage characteristics, percolation threshold, etc.), most probably, cannot be quantitatively interpreted within the framework of a conventional percolation model. We have explained the observed behavior by a two-level scale interaction in the system caused by (i) a significant geometric disparity between the constituent components and (ii) proximity-induced superconducting state of the half-metallic manganite.